Bridging the digital divide through public, school and college libraries: Case study of Bangladesh - Shuva, Nafiz Zaman; Akhter, Rowshon (Journal of the Bangladesh Association of Young Researchers, 2011)
The least developed and developing countries are combating against digital divide in order to keep the wheel of development rolling and escape from the vicious circle of poverty as digital divide is one of the key factors that can lead the poverty situation of these nations to an extreme level. In Bangladesh, the digital divide condition is severe. Therefore it is imperative for Bangladesh to take fruitful steps to bridge the digital divide and to ensure ICT facilities at the national level. Recently as government pledged to convert Bangladesh into Digital Bangladesh by 2021 which is the golden jubilee year of Bangladesh independence, several initiatives have been taken to overcome the digital divide and to produce future qualified generations. However, it has been observed that no worth mentioning project has been taken by any government that ensures proper development of public, school and college libraries. Government should realize the fact that complete development of the country is never possible unless we concentrate library based education. It is not possible for any government to ensure computer with internet connection to each and every family in Bangladesh, however, it is possible to ensure ICTs at school, college and public libraries. The author of this paper firmly believe that ensuring ICTs to public, school and college libraries will greatly reduce digital divide at the national level and will produce qualified, efficient, ICT competent future generations. In this paper an attempt has been made by the authors to show the existing digital divide in the country, current ICT scenario and core projects that have taken by government, non-government, donor agencies and other development organization. The main object of this paper is to show how public, school and college libraries can reduce digital divide at the national level. It is believed that coordinated, long-term, effective projects/programme to reduce digital divide will ensure peaceful, educated, qualified, ICT competent future generations. Key words: Digital Divide; ICT Scenario Bangladesh; Government Initiatives; Non-government initiatives; Public libraries; School libraries; College libraries. DOI: 10.3329/jbayr.v1i1.6839 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.49-77